SENI BUDAYA SEBAGAI UPAYA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERNILAI ESTETIKA - Mizan Khairusani (Universitas Islam Sultan Agung, 2020)
Education is a cultural process, in which education will greatly affect human continuity in religion, socialization, and culture. Education and cultural arts can never be separated because they influence each other, including cultural arts that shape the personality of an individual or group. Therefore, the process in education must have high-cultured wisdom in order to build attitudes, a balanced character of students from cognitive, affective, psychomotor results. More specifically, the purpose of Islamic education is to build character and good character. It is felt that Islamic education which is full of the meaning and beauty of God will be easily combined with elements of art and culture. Armed with this art and culture, an educator will be able to create an innovative, creative, fun learning process, because the learning has aesthetic values.Keywords: Art and Culture, Islamic Education, Aesthetic Values